Etnoenglish: Weaving Words, Stories and Life Projects of the Zenú People - Jaraba Ramirez, Diana Luz; Arrieta Carrascal, Adolfo (Íkala, Revista de Lenguaje y Cultura, 2012)
Colombian bilingual educative policies aim to develop communicative competences in all schools. However, these policies are rarely functional in multicultural communities, such as indigenous communities. At The San Antonio Abad indigenous school, the teaching of English was irrelevant for the students because they never engaged with learning the language. Due to this problem, an ethnographic study was carried out. This study allows us to integrate the identitarian elements of the community to the teaching and learning process of the English language. The results showed that the cohesive element of the community was the arrow cane weaving process. This permitted the implementation of a set of strategies called Etnoenglish, based on the discourse and interaction patterns related to the weaving craftsmanship process. The implementations of these strategies improved the motivation and English learning among the students.